Separation of binary mixtures based on gamma infinity data using [OMMIM][NTf2] ionic liquid and modelling of thermodynamic functions. (April 2018) - Chen, Jin-Yuan; Kang, Rong-Xue; He, Zhuang-Zhuang; Miao-Zhang,; Ge, Ming-Lan
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. The (gas-liquid) partition coefficients were calculated. The excess thermodynamic functions, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [OMMIM][NTf2 ] was determined. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). The linear free energy relationship (LFER) analysis of the results was performed. Abstract: Activity coefficients at infinite dilution ( γ i ∞ ) and (gas-liquid) partition coefficients ( K L ) for organic compounds (alkanes, alkenes, alkyl benzenes, acetonitrile, acetone, tetrahydrofuran, ethyl acetate, 1, 4-dioxane, chloromethanes, and alcohols) in the ionic liquid (IL) 1-octyl-2, 3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([OMMIM][NTf2]) have been measured by the gas-liquid chromatographic(GLC) method in the temperature range of (313.15 to 353.15) K. Density, ρ as a function of temperature for [OMMIM][NTf2] at pressure p = 101.3 kPa were measured. The values of the partial molar excess enthalpies at infinite dilution ( H ¯ i E, ∞ ) were derived from the temperature dependence of the γ i ∞ values. The entropies ( T r ef S ¯ i E, ∞ ) and Gibbs energies ( G ¯ i E, ∞ ) of organic solutes in [OMMIM][NTf2] at a reference temperature T r ef = 298.15 K were also calculated from the γ i ∞ values. The Hildebrand's solubility parameters of the IL [OMMIM][NTf2] were also determined by the regular solution theory (RST) combined with Flory "combinatorial" equation. The linear free energy relationship (LFER) analysis of the results was performed to disclose molecular interactions operating between the IL and the individual solutes. Selectivity ( S i j ∞ ) and capacity ( k j ∞ ) at infinite dilution at 323.15 K have been determined for n-hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ) and compared to literature values for [NTf2]-based ILs for the same separation problems. For three isomeric xylenes separation problems, S i j ∞ at 323.15 K was also obtained from the γ i ∞ values.